2018
DOI: 10.1152/ajprenal.00113.2018
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of prostaglandin E2 receptor 4 ameliorates nephrotoxic serum nephritis

Abstract: Prostaglandin E2 (PGE2) signaling is known to modulate inflammation and vascular resistance. Receptors of PGE2 [E-type prostanoid receptors (EP)] might be an attractive pharmacological target in immune-mediated diseases such as glomerulonephritis. We hypothesized that selective EP4 antagonism improves nephrotoxic serum nephritis (NTS) by its anti-inflammatory properties. Mice were subjected to NTS and treated with the EP4 antagonist ONO AE3-208 (10 mg·kg body wt−1·day−1] or vehicle starting from disease initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…Of the two positively expressed DEGs, PTGER4 (prostaglandin E receptor 4) encodes for prostaglandin (PG) E4, and PGE2 is known to induce cyclooxygenase (COX)-2 expression in podocytes via the PGE4 receptor [ 35 , 36 ]. Enhanced expression of E-prostanoid receptor 4 (EP4) in cultured podocytes was shown to negatively affect podocyte adaptation to mechanical stretch [ 37 ], while the inhibition of EP4 attenuated the development of nephropathy in rodent models [ 38 , 39 ]. Additionally, EP4 inhibition prevented the TGF-ß1-induced dedifferentiation of glomerular podocytes [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the two positively expressed DEGs, PTGER4 (prostaglandin E receptor 4) encodes for prostaglandin (PG) E4, and PGE2 is known to induce cyclooxygenase (COX)-2 expression in podocytes via the PGE4 receptor [ 35 , 36 ]. Enhanced expression of E-prostanoid receptor 4 (EP4) in cultured podocytes was shown to negatively affect podocyte adaptation to mechanical stretch [ 37 ], while the inhibition of EP4 attenuated the development of nephropathy in rodent models [ 38 , 39 ]. Additionally, EP4 inhibition prevented the TGF-ß1-induced dedifferentiation of glomerular podocytes [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced expression of E-prostanoid receptor 4 (EP4) in cultured podocytes was shown to negatively affect podocyte adaptation to mechanical stretch [ 37 ], while the inhibition of EP4 attenuated the development of nephropathy in rodent models [ 38 , 39 ]. Additionally, EP4 inhibition prevented the TGF-ß1-induced dedifferentiation of glomerular podocytes [ 39 ]. In our study, the marked upregulation of PTGER4 expression suggests that IL-4 may have triggered the EP4-induced pathogenic process.…”
Section: Discussionmentioning
confidence: 99%
“…For the evaluation of crescents, a minimum of 50 glomerular cross-sections were evaluated. PAS-positive material within glomeruli was scored according to a semiquantitative scoring system as published recently [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence that targeting EP4 in this disease model influences disease outcome. Our group recently showed that the EP4 antagonism protects mice from NTS by downregulation of chemokine (C-X-C motif) ligand (CXCL)-5 in tubular cells, thereby inhibiting the recruitment of neutrophil granulocytes to the kidney [ 29 ]. Interestingly, positive effects of EP4 agonists on the kidney phenotype have been described in the past without providing clear evidence of the exact mechanism [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…An EP4 receptor-derived peptide, which acts as a negative allosteric modulator, restored renal function in models of acute renal failure (Leduc et al, 2013), and EP4 antagonists prevented inflammation and renal impairment in a mouse model of acute glomerulonephritis (Aringer et al, 2018).…”
Section: Kidneymentioning
confidence: 99%